2017
DOI: 10.1302/0301-620x.99b5.37521
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E diffused highly cross-linked polyethylene in total hip arthroplasty at five years

Abstract: The five-year results showed that E1 polyethylene does not wear more than the control, ArComXL. This is the longest-term RCT comparing the wear performance and clinical outcome of vitamin E diffused HXLPE with a previous generation of medium cross-linked polyethylene. Cite this article: 2017;99-B:577-84.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…liners, where steady state wear rates between 1 and 10 µm/year have been found [19][20][21][22], and is considerably below the osteolysis threshold wear rate of 100 µm/ year [23]. Short-term follow-up studies of xlpe liners with vitamin e content also show similar wear rates as those from xlpe previously mentioned [16,17,24,25]. However, this excellent wear characteristics of the xlpe at the long-term are in question, as studies have demonstrated in vivo oxidation of annealed xlpe by means of cyclic fatigue loading and fluid absorption, whereas remelting of xlpe leads to a reduction of its mechanical properties [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…liners, where steady state wear rates between 1 and 10 µm/year have been found [19][20][21][22], and is considerably below the osteolysis threshold wear rate of 100 µm/ year [23]. Short-term follow-up studies of xlpe liners with vitamin e content also show similar wear rates as those from xlpe previously mentioned [16,17,24,25]. However, this excellent wear characteristics of the xlpe at the long-term are in question, as studies have demonstrated in vivo oxidation of annealed xlpe by means of cyclic fatigue loading and fluid absorption, whereas remelting of xlpe leads to a reduction of its mechanical properties [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 76%
“…as highly cross-linked polyethylene with vitamin e content (either blended or diffused) is a relatively new material, there are currently no long-term follow-up studies available to compare the results obtained in the current in vitro study. Nevertheless, short-term follow-up studies have shown a similar performance between xlpe liners with and without vitamin e content [16,17]. Vitamin e does not provide additional wear resistance to the polyethylene after highly crosslinking, but prevents its oxidation, and thus it is expected to maintain its excellent wear characteristics through time.…”
Section: Discussionmentioning
confidence: 99%
“…Other Level-I and II studies demonstrated significantly less wear for vitamin E-infused HXLPE compared with UHMWPE 20 , medium cross-linked polyethylene 21 , and HXLPE without vitamin E 22 at mid-term follow-up.…”
Section: Highly Cross-linked Polyethylene (Hxlpe)mentioning
confidence: 87%
“…As a consequence, the liner can also be thinner and larger heads can be used, with a possible improvement in joint stability. While the early clinical results are promising, with a low wear rate reported even with 36-mm diameter heads, the follow-up is still too short to evaluate potential clinical advantages over regular XLPE liners 34 - 36 and registry data show no difference between XLPE and Vitamin E XLPE. 5…”
Section: Conventional and Cross-linked Polyethylenementioning
confidence: 99%